Associations of Socioeconomic Status and Healthy Lifestyle With Incidence of Dyslipidemia: A Prospective Chinese Governmental Employee Cohort Study - Li, Ling; Ouyang, Feiyun; He, Jun; Qiu, Dan; Luo, Dan; Xiao, Shuiyuan (Frontiers in Public Health, 2022)
Objective To test whether primary lifestyles mediate associations of SES with incident dyslipidemia and to explore interaction relations of lifestyles and SES with incidence of dyslipidemia. Methods We included 9901 individuals at baseline from January 2018 to November 2019, and incidence data were updated to 31, December 2020. Dyslipidemia was defined as total cholesterol (TC) 6.2 mmol/l TC ≥or triglycerides (TG) ≥ 2.3 mmol/L or low-density lipoprotein cholesterol (LDL-C) ≥ 4.1 mmol/L or high-density lipoprotein cholesterol (HDL-C) <1.0 mmol/L; or physician diagnosed dyslipidemia or lipid-lowering drugs use.. Lifestyles, socioeconomic factors, personal characteristics was collected by a questionnaire. A latent class analysis based on education, family income and occupational position was used to assess the SES. Lifestyle score was calculated using cigarette smoking, alcohol consumption, physical activity and diet. Cox proportional hazard models and multivariate analyses were used to explore the associations. The mediation effect was evaluated using bootstrap method. Results Participant mean age was 36.5 years (SD = 0.11). The cumulative incidence of dyslipidemia was 11.0% over a mean follow-up of 13.4 months. Compared with participants of high SES, those with low SES had higher risk of incident dyslipidemia (hazard ratio 1.32, 95% confidence interval [CI]: 1.01-1.73), after adjusting for lifestyle scores and other covariates. The proportion mediated by lifestyles was 5.41% (95%CI: 4.17-7.11%). A significant additive interaction was found between lifestyles and SES, whereas association between lifestyle and incident dyslipidemia was stronger among those of high SES. Additionally, individuals with low SES and no or one healthy lifestyle behavior had a higher risk of developing dyslipidemia than those with high SES and 3 or 4 healthy lifestyles. Conclusion Unhealthy lifestyles play a small moderating role in socioeconomic inequity in incident dyslipidemia among Chinese governmental employees, suggesting promoting healthy lifestyles alone may not significantly reduce socioeconomic inequalities in health, and measures to address other social determinants of health should also be considered alongside.o